ANALISIS RASIO LIKUIDITAS DAN RASIO PROFITABILITAS DALAM RANGKA MENINGKATKAN KINERJA KEUANGAN (Kasus pada Perusahaan Kosmetik dan Barang Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia) - Feby Febrianti Yusa; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Industry is one sector which has an important role in the development of a country. One of the industries in Indonesia and its products have a lot of interest is the consumer goods industry with the specifications of cosmetics and household goods. This study aims to determine the company's performance, especially consumer goods industry cosmetics and household goods listed in the Indonesia Stock Exchange in 2010-2014 with financial ratio analysis and to find out which companies are performing better tailor. Financial ratios used are liquidity ratio (Current Ratio and Quick Ratio) and profitability ratio (Net Profit Margin, ROI, ROE). The object of this study is cosmetic and household goods listed on the Stock Exchange 20010-2014 year period, amounting to 5 (five) companies, namely PT. Kino Indonesia Tbk (KINO), PT. Martina Berto Tbk (MBTO), PT. Mustika Ratu, Tbk (MRAT), PT. Mandom Indonesia Tbk (TCID) and PT. Unilever Indonesia Tbk (UNVR). However, due to PT. Kino Indonesia Tbk is a company newly listed company on December 11, 2015, then the object of this research is PT. Martina Berto Tbk, PT. Mustika Ratu Tbk, PT. Mandom Indonesia Tbk and PT. Unilever Indonesia Tbk. The results showed that PT. Mandom Indonesia Tbk have better liquidity than other companies. As for the profitability of PT. Unilever Indonesia Tbk better in generating profits than any other company.Keywords: financial ratio, profitability ratio, liquidity ratio and financial performance